PENGARUH PEMBERIAN PROBIO_FMplus DAN PAKAN YANG MENGANDUNG PUTAK TERHADAP PERFORMANS PERTUMBUHAN AYAM BROILER FASE GROWER - Geti Marince Pahnael (Partner, 2020)
ABSTRACTPutak is one of the alternative energy sources that can  used in poultry ration. However, the utilization of putak is limited due to its anti-nutritional factors especially fibre that could affect the gut health. Thus, it is important to potential feed additives that can improve the health of the digestive tract as well as the digestibility. Probio_FMplus is symbiotic probiotics produced by the Kupang State Polytechnic, but the study of using this probiotics is still very limited. The objective of the present study was to evaluate the effect of Probio_FMplus on growth performance of grower broilers fed diet containing putak and without putak. Total of 192 unsex broilers were randomly alloted into 24 pens (8 birds/pen). The experimental design was 2x2 factorial randomized complete design. The treatments were R0P0 (control diet), R0P1 (diet containing no putak + Probio_FMplus), R1P0 (diet containing no putak + no Probio_FMplus),  R1P1 (diet containing  putak +  Probio_FMplus). The data was analysed by using general linear model SAS version 9.1 (2004). The results showed that interaction of probiotic and putak did not affect (P>0.05) body weight gain, feed consumption, and feed efficiency. Birds fed diet containing putak had higher (P<0.05) body weight gain compared to those fed diet without putak. No differences were found in birds fed given Probio_FMplus  and no Probio_FMplus . However, numerically birds received Probio_FMplus  had higher body weight gain. In conclusion, 1) supplementation of Probio_FMplus in diet containing putak and without putak did not affect growth performance of grower broilers, 2) Putak improved body weight gain of grower broilers. Numerically Probio_FMplus improved body weight gain of grower broilers. Key words: Probiotics, putak